Sustainable Development in Supply Chain Management: The Role of Organizational Learning for Policy Implementation. (29th December 2014) - Oelze, Nelly; Hoejmose, Stefan Ulstrup; Habisch, Andre; Millington, Andrew
Abstract: Implementing sustainable policies in supply chains is a significant challenge for businesses. Recent evidence has shown that failure to manage supply chains responsibly can have significant impacts on firms' reputation and financial performance. In this paper, we develop a conceptual framework, which focuses on organizational learning, and outline specific channels through which firms can generate learning processes and build appropriate capabilities to successfully implement social and environmental supply chain policies. Drawing on 57 in‐depth interviews from a cross‐sectional sample of seven UK and nine German companies, we empirically assess our conceptual framework in accordance with a grounded, in‐depth case study analysis approach. We find compelling evidence to suggest that organizational learning is an important factor for a successful implementation of sustainable supply chain management. Organizational learning is often established as a result of training, knowledge acquisition, stakeholder engagement and collaboration between intra‐organizational and inter‐organizational partners, including suppliers and NGOs. Nonetheless, our results also emphasize that firms often have few systematic processes through which organizational learning is developed, and that such learning processes are often ad hoc at best, which in turn has significant implications for the responsible supply chain practices. Copyright © 2014 John Wiley & Sons, Ltd and ERP Environment